Average Error: 0.0 → 0.0
Time: 8.7s
Precision: 64
\[\left(a - b\right) \cdot c\]
\[\left(a - b\right) \cdot c\]
\left(a - b\right) \cdot c
\left(a - b\right) \cdot c
double f(double a, double b, double c) {
        double r24013607 = a;
        double r24013608 = b;
        double r24013609 = r24013607 - r24013608;
        double r24013610 = c;
        double r24013611 = r24013609 * r24013610;
        return r24013611;
}

double f(double a, double b, double c) {
        double r24013612 = a;
        double r24013613 = b;
        double r24013614 = r24013612 - r24013613;
        double r24013615 = c;
        double r24013616 = r24013614 * r24013615;
        return r24013616;
}

Error

Bits error versus a

Bits error versus b

Bits error versus c

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[\left(a - b\right) \cdot c\]
  2. Final simplification0.0

    \[\leadsto \left(a - b\right) \cdot c\]

Reproduce

herbie shell --seed 1 
(FPCore (a b c)
  :name "(a-b)*c"
  (* (- a b) c))